Cost-sharing Mechanisms of the Health Care Systems in Selected EU States - a Comparative Analysis - Lis, Stanisław; Skuza, Krzysztof (Krakow Review of Economics and Management/Zeszyty Naukowe Uniwersytetu Ekonomicznego w Krakowie, 2015)
The article analyses the co-financing of health services in the health care systems of the countries of the European Union, which are based on different variations of the two main models: the insurance model and the national health care model. Comparative analysis of the characteristics of health care financing systems is the starting point for a presentation of the issue common to all countries, which is to seek ways to reduce the growth rate of public expenditures on health. One of the methods on the table is to have patients finance part of the health services delivered. However, the level and scope of co-financing of these services by patients vary widely between countries that use an insurance-based model and those with a national health service one. The article presents a critical analysis of policies and levels of patient co-participation in different types of health services in selected EU countries (including Poland), along with a comparison of the advantages and disadvantages of the different solutions.